Evaluation of transportation noise in urbanised areas. A case study - CALIXTO, Alfredo; PULSIDES, Cristiane; ZANNIN, Paulo Henrique Trombetta (Archives of Acoustics, 2014)
The paper describes a study of noise emission levels by roads inside an urban setting. For this purpose simultaneous measurements were performed: a) noise levels Leq, L10 and L90, b) vehicle flow and c) traffic composition. Vehicle flow and traffic composition have been used to estimate sound emission levels using mathematical models. Models were developed for two different situations, either as a function of a single variable (vehicle flow, VF), or as a function of two variables (VF and percentage of heavy vehicles, HV). Results of the prediction models agreed well with measured noise levels, especially for the model considering the two independent variables, VF and HV.